EFEKTIVITAS KOMUNIKASI PEMBELAJARAN MELALUI GOOGLE CLASSROOM DALAM PROSES PEMAHAMAN PESAN MAHASISWA UNIVERSITAS AHMAD DAHLAN - Rahman, Hanifah; Mufid Salim (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2021)
ABSTRACT When all countries were shocked by the coronavirus outbreak or Covid-19, World Health Organization (WHO) designated this incident as a pandemic. As a result, learning activities must be carried out online using learning media. One of the learning media used is Google Classroom. However, there are several problems or obstacles in using Google Classroom online. As students do not understand the message conveyed, communication becomes ineffective. This study aims to determine the effectiveness of learning communication through Google Classroom at Ahmad Dahlan University students. This study uses a quantitative method, namely the survey to Ahmad Dahlan University students who use Google Classroom as a learning medium. The data collection method used a questionnaire and obtained 150 valid respondents. From the simple linear regression test results, there is the effectiveness of learning communication through Google Classroom. The effectiveness has a value of 62.2%. So it can be concluded that using Google Classroom as a communication medium for student learning is effective for Ahmad Dahlan University students. This study suggests that lecturers and students take advantage of the comments feature in Google Classroom.